PERANCANGAN DAN IMPLEMENTASI APLIKASI DAN DATABASE UNTUK PEMBANGUNAN KORPUS BAHASA MADURA - Yaqin, Moh Ainul; Arifin, Mohamamad Nazir; Dewi, Nindian Puspita; Said, Badar; darmawan, irwan (Universitas Madura, 2024)
Madurese, as one of Indonesia's regional languages, faces significant challenges in the current digital era. The younger generation tends to switch to using Indonesian, resulting in a weakening and lack of digital reading sources in Madurese. The impact is not only felt in everyday life but also has an impact on the availability of resources and research related to the Madurese language. This article examines the urgent need for a comprehensive and structured Madurese language corpus to support language analysis and further research. In response to these problems, researchers are planning to develop a Madurese language corpus management application. This application is designed to facilitate research by providing a rich database for language analysis and the application of natural language processing technology in the context of the Madurese language. With the aim of making a positive contribution to the development and preservation of the Madurese language, this application is expected to make data collection and analysis easier for researchers who interested in Madurese. It is hoped that this effort will enrich our understanding of the Madurese language and promote the sustainability of Indonesia's linguistic richness.